Effects‐directed analysis (EDA) and toxicity identification evaluation (TIE): Complementary but different approaches for diagnosing causes of environmental toxicity. (26th July 2013) - Burgess, Robert M.; Ho, Kay T.; Brack, Werner; Lamoree, Marja
Abstract: Currently, 2 approaches are available for performing environmental diagnostics on samples like municipal and industrial effluents, interstitial waters, and whole sediments to identify anthropogenic contaminants causing toxicological effects. One approach is toxicity identification evaluation (TIE), which was developed primarily in North America to determine active toxicants to whole‐organism endpoints. The second approach is effects‐directed analysis (EDA), which has origins in both Europe and North America. Unlike TIE, EDA uses primarily in vitro endpoints with an emphasis on organic contaminants as the cause of observed toxicity. The 2 approaches have fundamental differences that make them distinct techniques. In EDA, the sophisticated and elegant fractionation and chemical analyses performed to identify the causes of toxicity with a high degree of specificity often compromise contaminant bioavailability. In contrast, in TIE, toxicant bioavailability is maintained and is considered critical to accurately identifying the causes of environmental toxicity. However, maintaining contaminant bioavailability comes with the cost of limiting, at least until recently, the use of the types of sophisticated fractionation and elegant chemical analyses that have resulted in the high specificity of toxicant diagnosis performed in EDA. The present study provides an overview of each approach and highlights areas where the 2 approaches can complement one another and lead to the improvement of both. Environ Toxicol Chem 2013;32:1935–1945. © 2013 SETAC